PROPOSED INTEGRATED MARKETING COMMUNICATION STRATEGY FOR BADAN TENAGA NUKLIR NASIONAL (BATAN) TO PROMOTE NUCLEAR ENERGY POTENTIAL IN INDONESIA - Axel Putra Hadiningrat, Mohamad
BATAN as a non-ministerial government agency have a task to conduct a research related to the development of nuclear technology in Indonesia as well as BATAN has a mandate to contribute to overcoming the energy crisis in Indonesia by proposing a plan to build a Nuclear Power Plant (NPP), which until now has entered the stage of consideration. However, these efforts are still hampered by government regulation No. 79 of 2014 which states that nuclear technology is the last priority for the government to be built, so that the plan and development of nuclear technology in Indonesia is still stagnant and there is no definite follow-up from the government. Thus, the role of BATAN as an institution responsible for the development of nuclear technology for energy, has become very political and were having less collaboration between the stakeholders and the public as a whole. The need for appropriate policy products, requires BATAN to develop a positive stigma from nuclear technology through the campaigns that they do. In this case, BATAN focused their campaign by promoting nuclear technology as not only for energy but for the welfare of the people. Comprehensive research preparations have been made by BATAN nevertheless, public and political acceptance is important in this case because the development of nuclear research, especially for the construction of nuclear power plants is a mutual agreement for Indonesia.